THE PROFILE OF LOCAL TOFU INDUSTRY IN TRENGGALEK REGENCY, EAST JAVA PROVINCE, INDONESIA - Nina Lisanty; Eko Yuliarsha Sidhi; Agustia Dwi Pamujiati (Jurnal Hexagro, 2022)
A study was aimed to determine the costs, revenues, and profits of the tofu industry in Nglongsor Village, Karangan District, Trenggalek Regency in one production period. The location was determined intentionally. The sampling method used was saturated sampling or census. The reason for choosing the area was because it is a well-known and distinctive tofu-producing area in Trenggalek. The results showed that the average value of soybean raw materials was 42 kilograms at the price of soybeans of IDR 8,500 per kilogram, producing 400 packs of tofu. The selling price of tofu per pack of 2 (or four pieces) of IDR 2,000. In one production period, the revenue earned was IDR800,000. With an average total production cost of IDR518,786, the profit earned was IDR 218.822. The value of the R/C Ratio was 1.38, which means that the tofu home industry business was declared feasible to be developed. The statistical tests for the profit and business feasibility variables stated that the research hypothesis was accepted.